Using Heuristic Methods in the Process of Retail Shops Placement in the Context of Marketing Communication Effect Maximisation - Tomáš Fašiang,; Pavel Gežík, (Communication Today, 2025)
The topic of this empirical study is focused on applying usage of heuristic methods in the process of retail shops placement as a starting point of putting into effect targeted communication of retail shops with a customer in their radius of action. Subsequently, maximisation of communication strategy’s effect is based on appropriate communication with the target market within a limited area determined by buying stream, which affects the target customers and influences their shopping decisions and the volume of realised purchases in the given retail shop. The study is based on two mutually interconnected levels of related knowledge. On the first level, it deals with an analysis of relationships between selected macroeconomic indicators in the Slovak Republic and points out their direct influence on development of retail takings as a basic economic premise of retail shop functioning. On the second level the authors focus on the specific application of heuristic methods in the field of optimisation of retail shops placement in the context of maximisation of their radius of action and target group service, in which an ideal precondition for targeted and efficient communication with a customer occurs. The aim of the contribution is to point out, using practical application of heuristic methods ADD and DROP, the optimisation possibilities of retail shops placement with special emphasis on delimitation of direct communication space. The aim of application of the above-mentioned methods is to practically use the outcomes of the realised research and obtained statistical data.